2015
DOI: 10.1038/cdd.2015.75
|View full text |Cite
|
Sign up to set email alerts
|

HIPK2 restricts SIRT1 activity upon severe DNA damage by a phosphorylation-controlled mechanism

Abstract: Upon severe DNA damage a cellular signalling network initiates a cell death response through activating tumour suppressor p53 in association with promyelocytic leukaemia (PML) nuclear bodies. The deacetylase Sirtuin 1 (SIRT1) suppresses cell death after DNA damage by antagonizing p53 acetylation. To facilitate efficient p53 acetylation, SIRT1 function needs to be restricted. How SIRT1 activity is regulated under these conditions remains largely unclear. Here we provide evidence that SIRT1 activity is limited u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(53 citation statements)
references
References 63 publications
(114 reference statements)
1
49
0
Order By: Relevance
“…HIPK2 interacts and phosphorylates SIRT1 at Ser682 after DNA damage. Phosphorylation of SIRT1 inhibits SIRT1 deacetylase activity on p53 which in turn potentiates apoptotic p53 target gene expression and DNA damage-induced apoptosis (Conrad et al 2015). SIRT1 is also ubiquitinated by MDM2 during DDR, and ubiquitination of SIRT1 affects its function in cell death and survival in response to DNA damage (Peng et al 2015).…”
Section: Possible Mechanisms Of Hdacs In Cancer Developmentmentioning
confidence: 99%
“…HIPK2 interacts and phosphorylates SIRT1 at Ser682 after DNA damage. Phosphorylation of SIRT1 inhibits SIRT1 deacetylase activity on p53 which in turn potentiates apoptotic p53 target gene expression and DNA damage-induced apoptosis (Conrad et al 2015). SIRT1 is also ubiquitinated by MDM2 during DDR, and ubiquitination of SIRT1 affects its function in cell death and survival in response to DNA damage (Peng et al 2015).…”
Section: Possible Mechanisms Of Hdacs In Cancer Developmentmentioning
confidence: 99%
“…P53 plays a vital role in the apoptotic signaling pathways, including membrane apoptotic signaling and mitochondrial apoptotic pathways, and affects the transcription and expression of many apoptosis-related cytokines in the nucleus [41]. SIRT1 reduces the transcriptional activity of p53, and blocks p53-dependent cell apoptosis caused by DNA damage [42].…”
Section: Discussionmentioning
confidence: 99%
“…The deacetylase Sirtuin 1 (SIRT1) suppresses cell death after DNA damage by antagonizing acetylation of p53 [76]. Conrad et al found that DNA damage initiates interaction between SIRT1 and HIPK2, which phosphorylates SIRT1 at Ser682 in response to lethal damage [54]. Phosphorylation of Ser682 inhibits SIRT1 activity in p53 acetylation and impacts expression of apoptotic p53 target genes and apoptosis.…”
Section: Roles Of Hipk2 In Ddrmentioning
confidence: 99%